2020
DOI: 10.2174/1874205x02014010095
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, Risk Factors, Mortality and Morbidity of Status Epilepticus in Children: A Retrospective Cross-Sectional Study in Tehran, Iran

Abstract: Background: Risk factors identification associated with status epilepticus is valuable in order to prevent morbidity and mortality in children. This study aimed to consider the etiology, risk factors, morbidity and mortality in children with status epilepticus. Methods: This retrospective cross-sectional study was performed on 119 patients aged from one month old to 15 years old. Patients’ data were recorded, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The similar study form India observed that socioeconomic status, parenting, social environment and interactions as a the strongest risks for poor cognitive performance in children (Zhang et al, 2020). Therefore, therefore is important to consider the aetiology and risk factors in the evaluation of morbidity in these children (Vafaee-Shahi et al, 2020). These could show the importance of these networks surrounding the children, safeguarding the wellbeing and the optimal child growth.…”
Section: Discussionmentioning
confidence: 92%
“…The similar study form India observed that socioeconomic status, parenting, social environment and interactions as a the strongest risks for poor cognitive performance in children (Zhang et al, 2020). Therefore, therefore is important to consider the aetiology and risk factors in the evaluation of morbidity in these children (Vafaee-Shahi et al, 2020). These could show the importance of these networks surrounding the children, safeguarding the wellbeing and the optimal child growth.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent 2020 retrospective cross-sectional study of 119 patient aged from one month to 15 years [39], the most common aetiologies were acute symptomatic and febrile SE occurred in 32.8% and 22.7% respectively and remote symptomatic in 16.8% aetiologies were the most common underlying causes of S.E. While in children less than 3 years old, the acute symptomatic aetiology and febrile status SE aetiologies were estimated as the most common, in most patients older than 3 years old the most common aetiology of SE was unknown.…”
Section: Aetiologymentioning
confidence: 99%
“…While in children less than 3 years old, the acute symptomatic aetiology and febrile status SE aetiologies were estimated as the most common, in most patients older than 3 years old the most common aetiology of SE was unknown. Furthermore, aetiology appears an important predictor of mortality and morbidity [39], (Table 2).…”
Section: Aetiologymentioning
confidence: 99%